Long-term follow-up after ESS and balloon sinuplasty: Comparison of symptom reduction and patient satisfaction. (3rd May 2016) - Koskinen, Anni; Myller, Jyri; Mattila, Petri; Penttilä, Matti; Silvola, Juha; Alastalo, Ismo; Huhtala, Heini; Hytönen, Maija; Toppila-Salmi, Sanna
Abstract: Conclusion This is the first controlled study of balloon sinuplasty's long-term efficacy with the follow-up time over 5 years. The results are in accordance with a previous 2-year-follow-up study. Both techniques retained the efficacy and patient satisfaction on average 6 years after the surgery. Background Endoscopic sinus surgery (ESS) and balloon sinuplasty are considered as a treatment for chronic rhinosinusitis (CRS) after a failure of conservative therapy. High cost and lack of long-term follow-up studies restrain the use of balloon sinuplasty. Objective The aim of this study was to compare long-term efficacy and satisfaction in CRS patients who had undergone maxillary sinus operation with either balloon sinuplasty or ESS technique. Previous or additional sinonasal operations were exclusion criteria. Materials and methods Study patients were recruited from 208 CRS-patients who underwent either ESS or balloon sinuplasty. Patients with nasal polyposis (gradus ≥ 2), previous sinonasal surgery, unilateral disease, or immune deficiency were excluded. Altogether 45 patients in the ESS group and 40 patients in the balloon group were included. Of these, 30 and 28, respectively, answered to a phone interview held on average 6 years after primary surgery. Symptom reduction and long-term satisfaction were evaluated by using symptom scores of 19 parameters altogether. Results Both groups experienced improvement in symptoms and were equally satisfied with the operation. The number of patient-reported acute exacerbations was higher among the balloon dilated patients. Also, the reduction of thick nasal discharge was less evident in the balloon sinuplasty group. Four patients in the balloon sinuplasty group underwent revision surgery. There were no revisions in the ESS group.